Design and Implementation of a Tri-Band Miniaturized Planar Inverted-F Antenna with Double Resonator for GPS Application - Bousselmi, A.; Gharsallah, A.; Vuong, T. P. (Engineering, Technology & Applied Science Research, 2019)
In this paper, a new planar inverted-F antenna is presented for GNSS applications and the DCS band. The proposed antenna structure is based on capacitive slots that achieve multiband behavior. The antenna has two resonators of dimensions (31mm×17mm×0.35mm) and (20.5mm×17.5mm× 0.35mm), a ground plane (60mm×17.5mm×0.35mm) and 6.5mm height. A prototype was implemented and good agreement was noticed between the simulation and test results, indicating three resonant frequencies, namely 1.176GHz, 1.8GHz and 2.8GHz. Radiation characteristics and diversity performance of the proposed structure is presented with detail.